The London 2012 Olympics and Lottery Funding: Impacts on Cultural Legacy in the UK. - Dabas, Laura (2008)
I chose this topic as I felt it would be extremely interesting to look into the London 2012 Olympics from this angle, considering the current international developments and the huge debate going on at the moment. It a controversial and original subject and raises various important and complex issues. I very much enjoyed exploring this topic and I feel writing this paper has opened my eyes in many different ways. My dissertation seeks to examine the impacts of the 2012 Olympic Games on cultural legacy in the UK and also addresses whether or not the Olympic Lottery Raid is putting local heritage at risk. In order to explore these research questions, my first step consists of four main chapters, in which I discuss General Funding for the London 2012 Olympics, Regeneration, the Lottery Funding debate and finally, the Cultural Olympiad. Then, my strategy for investigating the dissertation topic is mainly based on a focus group session (5 participants, as well as a survey conducted by email questionnaire (60 respondents, 3 age groups). The study was carried out between June and September 2008, which makes it all the more significant seeing as the Beijing Olympics were taking place at the time, and respondents took a great interest in the general subject. My findings show what UK residents actually think about London hosting the 2012 Olympics and how these Games will affect the country as a whole, obviously focusing on the cultural legacy aspect.